SAFEGUARDING HUMAN CAPITAL: THE RELATIONSHIP BETWEEN PERCEIVED ORGANIZATIONAL SUPPORT, JOB STRESS, AND TURNOVER INTENTION AMONG EMPLOYEES OF GF - Darmawan Budhiarto Jonathan; Achmad Fajar Hendarman (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examines the effects of Perceived Organizational Support (POS) and Job Stress (JS) on Turnover Intention (TI) among employees in Indonesia's fintech industry while addressing the limited use of organization-specific evidence in turnover intention research. Research Methodology: Guided by Social Exchange Theory and Conservation of Resources Theory, the study employed a quantitative cross-sectional design at a regulated fintech group operating in Indonesia. The research model was developed through the analysis of 30 employee exit interviews using thematic coding and subsequently validated through a census survey involving 183 employees. Data were analysed using IBM SPSS Statistics Version 25 and multiple linear regression. Results: POS significantly reduced turnover intention (β = −0.534, p < 0.001), whereas JS significantly increased turnover intention (β = 0.297, p < 0.001). Together, both predictors explained 53.2% of the variance in turnover intention (Adjusted R² = 0.527). Conclusions: Organizational support represents a stronger determinant of turnover intention than job stress in the fintech context. Limitations: The findings are based on a single organization and a cross-sectional design, limiting causal inference and generalizability. Contributions: This study contributes to turnover intention research by integrating organization-specific qualitative evidence with quantitative hypothesis testing, extending the application of Social Exchange Theory and Conservation of Resources Theory within Indonesia's fintech industry and providing evidence-based implications for employee retention.